From Deficit Delusion to the Fiscal Balance Rule. (IMF Working Papers; Working Paper, 1989)
Although the deficit is a useful construct for Keynesian analyses of fiscal policy, the deficit appears to be a less useful measure of fiscal policy within all but a restricted class of intertemporal neoclassical models. This paper suggests that the nature of deficits in a simple certainty model with nondistortionary policies, and the in settings with uncertain policy, distortionary policy, and liquidity constraints is, to a large extent, arbitrary. It then posits a more appropriate description of fiscal policy for the class of models in question, and proposes the economically meaningful 'fiscal balance rule' as an alternative to the economically arbitrary 'balanced budget rule' as a means of assessing whether fiscal policy is intergenerationally tight or loose.